2021
DOI: 10.3390/nano11051196
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Quantification of miRNA from the Biomolecular Corona on Mesoporous Silica Nanoparticles

Abstract: To understand the factors that control the formation of the biomolecular corona, a systematic study of the adsorption of several miRNAs shown to be important in prostate cancer on amine-functionalized mesoporous silica nanoparticles (MSN-NH2) has been performed. Process parameters including miRNA type, nanoparticle concentration, incubation temperature and incubation time were investigated, as well as the potential competition for adsorption between different miRNA molecules. The influence of proteins and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the last few years, the adsorption of a wider range of biomolecules on the surface of NPs has been studied. By coupling chromatographic methods and mass spectrometry, nanomaterials have been shown to adsorb small molecules such as lipids (Gunnarsson et al, 2018; La Barbera et al, 2020; Lee et al, 2018; Lima et al, 2020), amino acids (Pink et al, 2018) and oligonucleotides (Vidaurre‐Agut et al, 2021), with lipids being nowadays the most investigated. In a recent study, Chetwynd et al demonstrated that, similarly to PC, the corona of metabolites can vary significantly between silica, TiO 2 , and polystyrene NPs, indicating a possible role of surface chemistry of materials on their interactions with small molecules (Chetwynd et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, the adsorption of a wider range of biomolecules on the surface of NPs has been studied. By coupling chromatographic methods and mass spectrometry, nanomaterials have been shown to adsorb small molecules such as lipids (Gunnarsson et al, 2018; La Barbera et al, 2020; Lee et al, 2018; Lima et al, 2020), amino acids (Pink et al, 2018) and oligonucleotides (Vidaurre‐Agut et al, 2021), with lipids being nowadays the most investigated. In a recent study, Chetwynd et al demonstrated that, similarly to PC, the corona of metabolites can vary significantly between silica, TiO 2 , and polystyrene NPs, indicating a possible role of surface chemistry of materials on their interactions with small molecules (Chetwynd et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of in vivo‐formed coronas have recently appeared as well. [ 201,209–212 ] In this setting, other types of biomolecules including nucleic acids, [ 213 ] lipids, [ 214,215 ] sugars, [ 23 ] and small metabolites [ 216 ] are present and adsorb to the NPs, and take part in exchange processes that continuously modify the composition of the biomolecular corona. In their comprehensive LC‐MS/MS proteomic analysis, Hadjidemetriou et al.…”
Section: Key Issues Of Current Debatementioning
confidence: 99%
“…Studies of in vivo-formed coronas have recently appeared as well. [201,[209][210][211][212] In this setting, other types of biomolecules including nucleic acids, [213] lipids, [214,215] sugars, [23] and small metabolites [216] are present and adsorb to the NPs, and take part in exchange processes that continuously modify the composition of the biomolecular corona. In their comprehensive LC-MS/MS proteomic analysis, Hadjidemetriou et al [209] observed significant differences in protein composition in the coronas formed on PEGylated liposomes (with and without attached antibodies for targeting) in vitro (10 min incubation in CD-1 mouse plasma) and in vivo (NP recovery from CD-1 mice 10 min after intravenous injection).…”
Section: Dynamics Of the Protein Coronamentioning
confidence: 99%